The Age-Orientation of Social Policy Regimes in OECD Countries - Julia Lynch (Luxembourg Income Study (LIS), 2001)
This article presents a series of measures of the extent to which social policies in twenty-one OECD countries are oriented towards the support of elderly (over 65 or in formal retirement) and non-elderly (under 65 and not retired) population groups. Employing breakdowns by age in spending on social insurance, education and health, tax expenditures on welfare substituting goods, and housing policy outcomes, this article shows that countries tend to demonstrate a consistent age-orientation across a variety of policy areas and instruments. After correcting for the demographic structure of the population, Greece, Japan, Italy, Spain and the United States have the most elderly-oriented social policy regimes, while the Netherlands, Ireland, Canada and the Nordic countries have a more age-neutral repertoire of social policies. In identifying the age orientation of social policy as a dimension of distributive politics that is not captured by other welfare state typologies, this article suggests the need to develop new accounts of the development of welfare states that include the dimension of age.
Keywords: 330; Sozialpolitik; Öffentliche Sozialausgaben; OECD-Staaten; Alternde Bevölkerung